2020
DOI: 10.1080/19490976.2020.1863135
|View full text |Cite
|
Sign up to set email alerts
|

Serrated neoplasia in the colorectum: gut microbiota and molecular pathways

Abstract: Colorectal cancer (CRC) is a heterogeneous disease with different gene expression patterns. There are two major colorectal carcinogenesis pathways: conventional adenoma-carcinoma pathway and alternative serrated neoplasia pathway. Apart from the conventional pathway that is typically initiated by characteristic APC mutation and chromosomal instability, the serrated neoplasia pathway is mainly characterized by mutations of BRAF or KRAS, microsatellite instability (MSI), and CpG island methylator phenotype (CIMP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 83 publications
1
12
0
Order By: Relevance
“…Azoxymethane (AOM) 26 mice develop hyperproliferative colonic mucosa, aberrant crypt foci (ACF), and eventually carcinomas 27 . An AOM-dextran sulfate sodium 28 model is widely used to study colitis-associated colon cancer 29 . We next investigated the role of VDR in regulating Claudin-5 expression in the development of cancer using an AOM/DSS treated mouse models ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Azoxymethane (AOM) 26 mice develop hyperproliferative colonic mucosa, aberrant crypt foci (ACF), and eventually carcinomas 27 . An AOM-dextran sulfate sodium 28 model is widely used to study colitis-associated colon cancer 29 . We next investigated the role of VDR in regulating Claudin-5 expression in the development of cancer using an AOM/DSS treated mouse models ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Until now, a precise list of microorganisms involved in dMMR CRC has remained elusive. A recent study linked CRC microflora to tumor CMS via 16S rRNA analysis ( Kang et al, 2021 ). The study revealed that the relative abundances of Fusobacteria and Bacteroidetes were enriched in CMS1, while Firmicutes and Proteobacteria were decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Ma et al reported that colorectal tumor apoptosis is induced by sitosterol through promoting gut microbiota to produce SCFAs which display antiproliferative effects on human colorectal cancer cells via gene expression inhibition [ 26 ]. Also, the intestinal flora may promote serrated lesions through EGFR signaling, the induction of cellular proliferation, the activation of a tumor immunosuppressive microenvironment, and the induction of an inflammatory response [ 27 ]. ROC analysis suggested that Faecalibacterium , Collinsella, and Bacteroides may be potential biomarkers for CRC.…”
Section: Discussionmentioning
confidence: 99%